Long-term management of Fontan patients: The importance of a multidisciplinary approach - Martino, Diletta; Rizzardi, Caterina; Vigezzi, Serena; Guariento, Chiara; Sturniolo, Giulia; Tesser, Francesca; Salvo, Giovanni di (Frontiers in Pediatrics, 2022)
The Fontan operation is a palliative procedure that leads to an increased survival of patients with functionally single ventricle. Starting from 1967, when the first operation was performed by Francis Fontan, more and more patients reach adulthood and is expected that in the next 20 years, the population with Fontan circulation will reach 150.000 subjects. The absence of a ventricular propulsion and the inability to control cardiac output, are the main problems of Fontan circulation, but potential complications involve not only the heart but also multiple organ systems, including the liver, lungs, brain, bones, and lymphatic system. As these patients are currently managed primarily by pediatric cardiologists, it is important to assure appropriate transition to adult care with involvement of a multidisciplinary team including adult congenital cardiologist and multiple subspecialists, many of whom are not familiar with the pathophysiology or the end-organ consequences of the Fontan circulation. Therefore, the authors conducted a review of literature to identify both gaps in knowledge on pathophysiological mechanisms and best available evidence on management of Fontan’s complications, with the aim of providing a model of follow-up based on a multidisciplinary patient centered approach.